The positive impact of Covid19 on Tuberculosis endemic areas - Farhan Ali; Kashif Ali (Journal of the Pakistan Medical Association, 2021)
During a pandemic, we see that the world has controlled covid19 by taking necessary measures. Covid19 and tuberculosis (TB) have mainly the same mode of transmission. The efforts, we took to eliminate covid19, could also be taken to decrease TB. Here, I proposed a strategy that could help to deal with TB suspected cases and to avoid exposure to other people who are coming in hospital setups. Continuous...